Durability evaluation of calcined clay and limestone powder blended ternary self-compacting concrete - Taku J. K; Amartey Y. D.; Ejeh S. P.; Lawan A. (Журнал інженерних наук)
This research work investigates the durability-based properties of a ternary calcined clay and limestone powder blended Self Compacting Concrete by measuring the short- and long-term permeation properties using water absorption and sorptivity properties testing. Also, the variation of compressive strength with age was evaluated at 7, 14, 28 and 56 days, while the split tensile strength was determined at 7 and 28 days curing. The Mineralogy and morphology of the ternary SCC was evaluated using FT IR Spectroscopy, SEM imaging and EDS. The results obtained shows that the ternary SCC showed improved durability and strength properties with age with dense and improved microstructure.